Can Transcranial Direct-Current Stimulation Alone or Combined With Cognitive Training Be Used as a Clinical Intervention to Improve Cognitive Functioning in Persons With Mild Cognitive Impairment and Dementia? A Systematic Review and Meta-Analysis - Cruz Gonzalez, Pablo; Fong, Kenneth N. K.; Chung, Raymond C. K.; Ting, Kin-Hung; Law, Lawla L. F.; Brown, Ted (Frontiers in Human Neuroscience, 2018)
Background: Transcranial direct-current stimulation (tDCS) facilitates cognitive improvement in healthy and pathological populations. It has been increasingly used in cases of mild cognitive impairment (MCI) and dementia. Our research question is: Can tDCS serve as a clinical intervention for improving the cognitive functions of persons with MCI (PwMCI) and dementia (PwD)? Objective: This systematic review evaluated the evidence from all published trials of tDCS on cognitive functions among PwD and PwMCI. Methods: A systematic review was conducted of studies published up to November 2017 involving tDCS in cases of MCI and dementia. Studies were ranked according to the level of evidence (Oxford Centre for Evidence-Based Medicine) and assessed for methodological quality (Risk of Bias Tool in the Cochrane Handbook for Systematic Reviews of Interventions). Data were extracted on all protocol variables to establish a reference framework for clinical interventions. Four randomized control trials with memory outcomes were pooled using the fixed-effect model for the meta-analysis. Results: Twelve studies with 195 PwD and four with 53 PwMCI met the inclusion criteria. Eleven articles were ranked as Level 1b. The results on the meta-analysis on pooled effects of memory indicated a statistically significant medium effect size of 0.39 (p = 0.04) for immediate effects. This improvement was not maintained in the long term 0.15 (p = 0.44). Conclusion: tDCS improves memory in PwD in the short term. It seems to have a mild positive effect on cognition in PwD and PwMCI but there is no conclusive advantage in coupling with cognitive training. More rigorous evidence is needed to establish whether tDCS can serve as an evidence-based intervention for both populations.